2019
DOI: 10.1038/s41390-019-0341-8
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal nutritional intakes and hyperglycemia as determinants of blood pressure at 6.5 years of age in children born extremely preterm

Abstract: BackgroundAdverse developmental programming by early-life exposures might account for higher blood pressure (BP) in children born extremely preterm. We assessed associations between nutrition, growth and hyperglycemia early in infancy, and BP at 6.5 years of age in children born extremely preterm.MethodsData regarding perinatal exposures including nutrition, growth and glycemia status were collected from the Extremely Preterm Infants in Sweden Study (EXPRESS), a population-based cohort including infants born <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
2
19
0
1
Order By: Relevance
“…In a previous study of the EXPRESS cohort, increased intakes of carbohydrates and hyperglycemia during the neonatal period were significantly and independently associated with higher systolic and diastolic blood pressures at 6.5 years of age [14]. In the present study, total and parenteral carbohydrate intakes were linked to smaller aortic annulus of the LV outflow tract, and hyperglycemia in the neonatal period was associated with increased LV wall thickness at a 6-year follow-up.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In a previous study of the EXPRESS cohort, increased intakes of carbohydrates and hyperglycemia during the neonatal period were significantly and independently associated with higher systolic and diastolic blood pressures at 6.5 years of age [14]. In the present study, total and parenteral carbohydrate intakes were linked to smaller aortic annulus of the LV outflow tract, and hyperglycemia in the neonatal period was associated with increased LV wall thickness at a 6-year follow-up.…”
Section: Discussionsupporting
confidence: 66%
“…Undernutrition and nutritional imbalances may have long term consequences. Both neonatal hyperglycemia and higher carbohydrate intake during the first eight postnatal weeks were associated with increased blood pressure at 6.5 years of age in children born extremely preterm [14]. Lewandowski et al reported that breast-milk consumption in preterm-born neonates was associated with increased ventricular end-diastolic volume index and stroke volume index later in young adulthood [15].…”
Section: Introductionmentioning
confidence: 99%
“…9 The reduction in hyperglycaemia, which has been associated with increased risk of multiple neonatal morbidities as well as poor growth, also has the potential to improve childhood outcomes in the longterm. 28 Clinical management in the intervention group was based on the ability to be guided by trends in glucose concentrations shown by the realtime CGM data and did not require blood glucose concentrations to be checked before altering treatment. However, the advice on checking blood glucose concentrations when there was a rapid change in CGM values or if CGM values fell to less than 4 mmol/L was key to ensuring a safe decision system and resulted in unanticipated hypoglycaemia being detected.…”
Section: Discussionmentioning
confidence: 99%
“… 9 The reduction in hyperglycaemia, which has been associated with increased risk of multiple neonatal morbidities as well as poor growth, also has the potential to improve childhood outcomes in the long-term. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Inclusion and exclusion criteria for EXPT, perinatal characteristics, data on survival, neonatal morbidity, neurodevelopmental outcomes at 30 months and 6.5 years-of-age, as well as details on lung function, vascular assessments and left ventricular functions in childhood have previously been reported [ 2 , 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Twelve EXPT children were excluded due to congenital heart malformations, and CTRL children were only invited if they had a history of a normal neonatal period without any diagnoses of congenital malformations or ongoing cardiovascular or pulmonary disease.…”
Section: Methodsmentioning
confidence: 99%